Relationship of plant diversity and livelihood of homestead farmers in Rangamati sadar upazila of Bangladesh: Plant Diversity & Homestead Livelihood in Rangamati Sadar Upazila (Journal of the Sylhet Agricultural University, 2025)
Bangladesh's economy heavily relies on homestead agroforestry. In Sadar upazila of Rangamati in Bangladesh, the study was conducted to ascertain the effect of homestead agroforestry on the respondents’ standard of living. It also identifies how the selected variables, like age, education, family size, farm size, homestead size, annual revenue, expenditures, and knowledge of homestead farmers, relate to the diversity of plant species in the study area. Data was collected using structured interviewing, and a correlation test was carried out to determine the relationship between the relevant dependent and independent variables of the study. Education, Farm size, Homestead size, Annual income, Expenditure, and Savings of the respondents revealed significant positive relationships with the plant species diversity, whereas no such relationship was observed with Age, Family size, Knowledge of Homestead Agroforestry and Socio-economic conditions of those respondents. Male were the highest decision makers for housing with 37.5% while female were highest decision makers for tree plantations, Schooling, Savings and Expenditure, and Participation in training program, Uses of agroforestry product and Agronomic crop with 35%, 41.67%, 36.67%, 44.17% and 35.83%, respectively. In the case of family planning, decisions were equally made by males, females, and both males and females combined, accounting for 33.33%. . Therefore, there is a huge opportunity to increase the farmers' income and their livelihood through increasing plant diversity in the present homestead areas of Bangladesh.J. Sylhet Agril. Univ. 11(2): 35-42, 2024